What Counts as "Violence?" Semantic Divergence in Cultural Conflicts. Issue 2 (1st February 2023) - Boches, Daniel J.; Cooney, Mark
ABSTRACT: In times of conflict, the meaning of words tends to fluctuate. For example, the word "violence" traditionally refers to physical force against people or property. However, some have expanded the term "violence" to include non-force (e.g., speech). Conversely, others have actively avoided the "violence" label to describe clear instances of force (e.g., property destruction). When the definitions of concepts expand and contract, semantic divergence – the degree of disagreement over the meaning of words – increases. Drawing on the work of Donald Black, we derive a partial explanation for the semantic divergence of "violence" labeling in cultural conflicts. First, at the macro-level, as social intimacy and inequality have declined over the past few hundred years, violence has become increasingly stigmatized, rendering an allegation of "violence" a potentially powerful weapon for deployment against cultural opponents. Second, at the case-level, social distance and partisanship, fostered by the internet, combine to produce social polarization – factions internally close but externally distant – of which a predictable result is the semantic divergence of "violence."